Beyond gluten-free diet: a critical perspective on phase 2 trials on non-dietary pharmacological therapies for coeliac disease - Scalvini, Davide; Scarcella, Chiara; Mantica, Giulia; Bartolotta, Erica; Maimaris, Stiliano; Fazzino, Erica; Biagi, Federico; Schiepatti, Annalisa (Frontiers in Nutrition, 2025)
Coeliac disease is an immune-mediated chronic enteropathy, with a prevalence of around 1% in the general population and occurring in genetically susceptible individuals after the ingestion of gluten proteins present in wheat, rye and barley. Currently, a strict lifelong gluten-free diet is the cornerstone of treatment of coeliac disease. However, maintaining strict dietary adherence is challenging for many patients, due to the high costs, the highly restrictive nature of the diet and the impact on patients’ quality of life. Moreover, a tiny minority of coeliac patients can develop pre-malignant/malignant complications of coeliac disease, a group of conditions, that despite being rare, are still burdened by a poor prognosis due to the lack of effective therapies. Therefore, the development of pharmacological treatments as an alternative to or supportive of a gluten-free diet is still an unmet need. The identification of new pathogenetic targets in the last years has enabled the development of several candidates molecules, many of which have been investigated in phase 2/3 clinical trials. In this narrative review we aim to summarise the investigational therapies that have been evaluated in phase 2/3 trials and provide a critical overview on the latest advances in this field.